PEMANFAATAN LIMBAH PELEPAH KELAPA SAWIT (Elaeis guineensis Jack) SEBAGAI MEDIA TANAM SAWI PAKCHOY SAMHONG F1 (Brassica rapa L) - Yusmaidar Sepriani (JURNAL AGROPLASMA, 2019)
Planting pakchoy samhong king f1 organically using planting media of waste compost from the midst of municipal waste. The research was conducted in Aek Paing Village, North Rantau District Labuhanbatu District. This study aimed to determine the provision of compost Waste Palm Plants to the growth of mustard plants in the Greenhouse. This research used descriptive analysis research method. The results showed that compost wastewater palm oil increased the weight and width of the leaves compared without the use of compost Palm Waste. Planting Organically mustard vegetables are more effective and efficient. Keywords: compost, mustard, organic plant.